(untitled) (Research, Society and Development, 2017)
This study sought to present a food insecurity situation experienced by families living in the Terra Nova community of the municipality of Massapê in the State of Ceará, Brazil. It is a quantitative study with transversal approach. A questionnaire was used to evaluate the socio-demographic characteristics, along with the Brazilian Scale of Food Insecurity - BSFI - with 15 food insecurity questions at different levels of intensity. We searched 28 families and obtained information on family income, socioeconomic status, housing, basic sanitation, schooling and food consumption. The prevalence of food insecurity in households with residents aged over 18 was 75%, 25% mild, 50% moderate and 0% severe. For households with at least one resident under the age of 18, the prevalence of food insecurity was 100%, being 41.67% mild, 50% moderate and 8.33% severe. More than a half of the families (75%) lived with up to ½ minimum wage per month. The majority of families (82,15) reported being beneficiaries of an income transfer program, in this case, Bolsa Família. The results show that although there are public policies to combat hunger in Brazil, there are still many families residing, mainly in the Northeast, who live in situations of social vulnerability. Therefore, it is necessary and essential to create and implement structuring actions that can reverse this situation, both regarding food production, as well as access to food of sufficient quality and quantity to address such deficiencies.